2014
DOI: 10.1049/mnl.2014.0275
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of the stainless steel surface with super durable one‐direction superhydrophobicity and two‐direction anisotropic wettability

Abstract: Inspired by the anisotropy of the rice leaf surface, high-speed wire electrical discharge machining (HS-WEDM) technology was used to build submillimetre-scale structures on the 304 stainless steel surfaces, and fluorination treatment was applied on the resulting surfaces. The wettability and microstructure of the resulting surfaces were investigated by a large depth 3D scanner, scanning electron microscopy and by the contact angle measuring instrument. The durability of the fabricated surface was evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…In our work, HS-WEDM (DK7732) was used to fabricate the stainless steel surface with the anisotropic wettability [20]. First, a HS-WEDM was used to fabricate the microstructure on Al substrates.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In our work, HS-WEDM (DK7732) was used to fabricate the stainless steel surface with the anisotropic wettability [20]. First, a HS-WEDM was used to fabricate the microstructure on Al substrates.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…With the increasing of the bareness time in air, the surface energy was decreased continuously, which made the contact state between the droplet and the sample surface transform into Cassie theoretical model. Considering that microstructures with thin films are known to stabilise Cassie states [18], this would be expected to amplify the hydrophobicity of the rough substrate.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The results showed that the groove direction led to nonuniform wettability with anisotropic properties [ 26 , 27 ]. Wan et al also found two-direction anisotropy of the superhydrophobic property on steel surfaces with V-shaped grooves [ 28 ]. Wan et al used high speed wire EDM and chemical etching to fabricate micro/nanometer-scale rough structures on an Al alloy surface [ 29 ].…”
Section: Introductionmentioning
confidence: 99%